John Toland : his methods, manners and mind - Daniel, Stephen H. (Stephen Hartley), 1950- (McGill-Queen's studies in the history of ideas, 1984)
Drawing on a variety of published and unpublished material representing Toland's broad interests, Professor Daniel reveals a common theme emphasizing man's capacity for independent thought on basic philosophical, religious, and political issues. Roughly chronological, Daniel's treatment describes Toland's progressive refinement of this fundamental aspect of his thought. After examining, in his early works, the process whereby religion becomes mystified, Toland turned to biography, demonstrating that through it one can regain rational control over religion. Prejudices and superstitions, topics of the Letters to Serena, are shown to be overcome through corrections implicit in the principles of biographical and historical exegesis. Polemic as philosophic methode required Toland to provide a doctrine of esoteric communication. In the course of his later writings this doctrine became grounded in a metaphysics suitable for the Cieronian religion of the pantheists.